Promoting student interest in science: The impact of a science theatre project - Schulze Heuling, Lydia (LUMAT: International Journal on Math, Science and Technology Education, 2021)
Researchers have often noted the potential of the performing arts to support STEM education – especially in heterogeneous classrooms. This article reports on the implementation of a science theatre project in a secondary school class located in a disadvantaged area of Hamburg (Germany). In the accompanying research study, effects on students’ interest in STEM and artistic expression were surveyed. Data analysis using t-tests shows that the artistic work significantly increased students’ interest in physics and chemistry, and specifically in the process of galvanization, the project’s focus topic. The analysis also revealed a growth in students’ knowledge of cultural practices, self-confidence, joy in individual artistic expression, and classroom spirit during the course of the project.